General trends of accident rate in Vilnius city when implementing transport humanization and forming the functionally integrated urbanistic structures - Paliulis, Grazvydas Mykolas; Valeika, Vidualdas; Skrodenis, Egidijus (International Conference “Environmental Engineering”, 2017)
The paper concerns the present situation of road safety in Vilnius City, the capital of Lithuania of road safety in Vilnius City, the capital of Lithuania. Vilnius has the largest number of vehicles and the largets level of car ownership in Lithuania. The detailed analysis and audit of accidents in Vilnius City enabled to determine general trends of accident rate and the black spots, to estimate the effect of measures implemented and their general trends, to identify street sections and intersections with the highest accident concentration. The number of fatal and injury accidents in Vilnius City has been considerably decreasing since 2007 (1029 accidents). In 2015, 596 accidents occurred where 18 road users were killed and 671 were injured. In 2015, compared to 2014, the number of fatal and injury accidents in Vilnius decreased by 7.17 %, the number of people killed – by 31.38 % and of people injured – by 5.36 %.